Adherence to a Healthy Lifestyle Among Hypertensive Patients Based on Social Cognitive Theory in a Private Hospital in Bogor - Wiraandini, Ni Putu Devi; Ramatillah , Diana Laila (Jurnal Locus Penelitian dan Pengabdian, 2025)
Introduction: Hypertension management relies heavily on lifestyle modification, yet many patients remain non-adherent to healthy behaviours. This study aimed to assess the influence of sociodemographic, personal, and environmental factors on healthy lifestyle adherence among hypertensive patients, using the Social Cognitive Theory (SCT) framework. Methods: A cross-sectional study was conducted in July 2024 at a private hospital in Bogor, involving 239 hypertensive outpatients. Validated questionnaires assessed self-efficacy, self-regulation, social support, and adherence behaviours. Data were analyzed using Chi-square and Fisher’s Exact tests (p < 0.05). Results: Significant associations were found between age, BMI, number of children, and family history of hypertension with motivation, self-efficacy, self-regulation, social support, and lifestyle adherence. Age was significantly linked to motivation (p = 0.001), self-efficacy (p = 0.001), and self-regulation (p = 0.005). BMI correlated with illness perception (p = 0.002), self-regulation (p = 0.025), and adherence (p = 0.004). Number of children and family history of hypertension were also significantly related to multiple behavioural factors. Gender, education, and occupation showed no significant effects. Conclusion: Adherence to a healthy lifestyle among hypertensive patients is significantly influenced by age, BMI, number of children, and family history. SCT-based interventions should target personal and familial factors to improve lifestyle adherence and hypertension outcomes.